Perception of Stake Holder About Graduates’ Profile and Its Implications for Curriculum Development - Erlina, Erlina; Khoirurrijal, Khoirurrijal; Wahab, Muhbib Abdul; Hijriyah, Umi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
Master study program of Arabic Education (PBA) in UIN Raden Intan Lampung Postgraduate was established in 2017. The draft curriculum for this study program has not been reviewed and validated according to the needs of the graduates. In the curriculum, a formulation of graduates’ profile is needed. This research aims to determine the perceptions of Stakeholders about the profile of master study program of Arabic Education (PBA) graduates of UIN Raden Intan Lampung is as their expectation and the demand of the IQF (Indonesian Qualification Framework) level 8 in applied master program.This research was conducted in qualitative with Survey method. Data collection instruments include questionnaires, interviews and documentation. Data is analyzed in qualitative. The survey results of stakeholders are known that the profile of the main graduates of master study program of Arabic Education (PBA) in UIN Raden Intan Lampung Postgraduate is as a teacher of Arabic in the Bachelor program (S1), supporting profiles as researchers, Arabic Education designers and the preferred profiles as Arabic philologists or journalists. The formulation of the Graduate Profile has implications for curriculum development and the preparation of the documents.